Extracellular vesicles as advanced therapeutics for the resolution of organ fibrosis: Current progress and future perspectives - Lv, Ke; Wang, Yizhuo; Lou, Peng; Liu, Shuyun; Zhou, Pingya; Yang, Li; Lu, Yanrong; Cheng, Jingqiu; Liu, Jingping (Frontiers in Immunology, 2022)
Organ fibrosis is a serious health challenge worldwide, and its global incidence and medical burden are increasing dramatically each year. Fibrosis can occur in nearly all major organs and ultimately leads to organ dysfunction. However, current clinical treatments cannot slow or reverse the progression of fibrosis to end-stage organ failure, and thus advanced anti-fibrotic therapeutics are urgently needed. As a type of naturally derived nanovesicle, native extracellular vesicles (EVs) from multiple cell types (e.g., stem cells, immune cells, and tissue cells) have been shown to alleviate organ fibrosis in many preclinical models through multiple effective mechanisms, such as anti-inflammation, pro-angiogenesis, inactivation of myofibroblasts, and fibrinolysis of ECM components. Moreover, the therapeutic potency of native EVs can be further enhanced by multiple engineering strategies, such as genetic modifications, preconditions, loading with therapeutic reagents, and in combination with functional biomaterials. In this review, we briefly introduced the pathology and current clinical treatments of organ fibrosis, discussed EV biology and production strategies, and particularly focused on important studies using native or engineered EVs as interventions to attenuate tissue fibrosis. This review will provide insights into the development and translation of EV-based nanotherapies into clinical applications in the future.